2015
DOI: 10.1186/s13075-015-0757-4
|View full text |Cite
|
Sign up to set email alerts
|

CDP7657, an anti-CD40L antibody lacking an Fc domain, inhibits CD40L-dependent immune responses without thrombotic complications: an in vivo study

Abstract: IntroductionCD40 ligand (CD40L) blockade has demonstrated efficacy in experimental autoimmune models. However, clinical trials of hu5c8, an anti-human CD40L IgG1 antibody, in systemic lupus erythematosus (SLE) were halted due to an increased incidence of thrombotic events. This study evaluated CDP7657, a high affinity PEGylated monovalent Fab' anti-CD40L antibody fragment, to assess whether an Fc-deficient molecule retains efficacy while avoiding the increased risk of thrombotic events observed with hu5c8.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 31 publications
5
72
0
Order By: Relevance
“…The Fc portion of the full-length antibody has a critical role in the mechanism leading to thromboembolic events 17 18. Since dapirolizumab pegol lacks the Fc portion, it would not be expected to be associated with increased thromboembolic risk, a hypothesis supported by the absence of thromboembolic events in the present study and a previous non-human primate study in Rhesus monkeys 19. Multiple doses of dapirolizumab pegol were well tolerated.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The Fc portion of the full-length antibody has a critical role in the mechanism leading to thromboembolic events 17 18. Since dapirolizumab pegol lacks the Fc portion, it would not be expected to be associated with increased thromboembolic risk, a hypothesis supported by the absence of thromboembolic events in the present study and a previous non-human primate study in Rhesus monkeys 19. Multiple doses of dapirolizumab pegol were well tolerated.…”
Section: Discussionsupporting
confidence: 69%
“…It is proposed that the observed treatment-related (TR) thromboembolic events occurred as a result of platelet activation and aggregation, due to the formation of anti-CD40L antibody and soluble CD40L immune complexes that tether to platelets via binding of sCD40L to surface-expressed CD40 and activate platelets through interactions of the Fc with Fc gamma receptor IIA on the platelet surface 17 18. Dapirolizumab pegol (CDP7657), an anti-CD40L Fab’ antibody fragment conjugated to polyethylene glycol (PEG),19 was designed to address the potential safety problems caused by the Fc moiety, while retaining favourable pharmacokinetics (PK). In vitro assays have demonstrated that dapirolizumab pegol is a potent antagonist of CD40L binding to CD40, and dose-dependent inhibition of antibody responses with dapirolizumab pegol have been demonstrated in both humanised severe combined immune deficient mice and cynomolgus macaques 19 20.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the severe RA condition in the control group (RA8) might induce thickening of the intima layer in pulmonary arteries. In contrast to human and nonhuman primate platelets, mouse platelets do not express FcRs 34 . Furthermore, the amount of blood that can be sampled is not sufficient to examine blood parameters serially due to the small body size of mice.…”
Section: Discussionmentioning
confidence: 83%
“…28 CD32a likely mediated such thrombosis. 29 Hypothermia resulting from injection of a CD32a-activating mAb in FCGR2A mice was first reported by Taylor and colleagues in 2000. 25 In 2005, a report by van Royen-Kerkhof et al showed that MDE-8 prevented hemolytic anemia in CD32a-Tg mice lacking functional CD16, CD64, and FcgRIV, but did not address the possibility of anaphylaxis had such FcgRs been present.…”
Section: Discussionmentioning
confidence: 93%